Applications of innovative composite materials for seismic strengthening of masonry structures - Micelli, Francesco (Alternativas, 2017)
Masonry buildings are prone to brittle collapses under seismic forces due to their fragility and low capacity to resist against cyclic actions. In most cases failures occur in forms of rigid collapses due to loss of equilibrium of entire structural parts, and this is due to low quality of structural detailing or horizontal forces due to vaults and arches that increase their intensity during earthquakes. The entire architectural heritage is represented by masonry construction, also in seismic areas, thus a mandatory issue consists of preserving the historical value against natural events such as earthquakes. In the last years new materials were employed as strengthening systems for structural purposes, and composite materials are those that have found a large field of application in this context. New structural solutions for seismic strengthening and retrofit are presented in the paper, with reference to real applications in which composite materials demonstrated to be effective solutions. The applications will be presented with reference to two historical masonry buildings, having different construction schemes; in which pre tensioned FRP wires were designed and applied as ties. The use of FRP wires for the first building was studied with reference to the existing cracking problems, which were investigated by means of non-destructive techniques, visual inspections and local destructive tests. The second case reports a study of seismic vulnerability for a large building used as theatre, in which a global analysis was accompanied by kinematic analyses that were run under linear and non- linear approaches. The results of the analyses allowed understanding the possible failure mechanisms that needed to be inhibited by an effective structural strengthening system. Also in this case the use of FRP pre-tensioned wires, about 40 m long, demonstrate to be the most effective structural device in terms of costs and speed of application. The seismic analyses (global and local) will be illustrated and discussed in the paper, with reference to the experimental tests that were necessary for the characterization of the material properties. The results will show how the presence of the FRP system is able to prevent possible collapses of the high walls that are present in the building.